Regulation of photosynthetic characteristics carbon and nitrogen metabolism and growth of maize seedlings by graphene oxide coating - Xu Zhang; Weidong Huang; Deyong Kong; Wei Guo; Haiyan Sun (Scientific Reports)
Abstract Maize seedlings in cold regions and high latitude often face abiotic stress. As a result, weak seedlings affect maize production, The commonly used seed coating agents in production are mainly to prevent biological stress of pests and diseases, and have little effect on seedling vigor and abiotic resistance. In this experiment, the combination of graphene oxide (GO) and seed coating agent can effectively prevent pests and diseases and increase the growth of seedlings.The effects of different concentrations of composite GO seed coating agent on photosynthetic carbon and nitrogen metabolism activity of maize were verified by pot experiments. It provides a reference for the application of nanomaterials in maize seed adjuvant technology and the improvement of maize seedling quality. Using maize as a model plant, the study evaluates, 22 g/L(T1), 44 g/L(T2), 66 g/L(T3), and 88 g/L(T4), GO were add respectively. Commercial seed coating agent as control (Con). Under the conditions of this experiment, GO thickened the stem by regulating the nutrients absorption of the roots in maize seedlings. The leaf thickness and vascular bundle area were increased, the photosynthetic efficiency of leaves were improved. Finally, it promoted the carbon and nitrogen metabolism of maize seedling leaves. Therefore, 44 g/L GO is the most suitable concentration as a coating agent in this experiment.